Pengaruh Brand Trust dan Brand Experience Terhadap Brand Loyalty pada Produk Eiger di Kota Malang - Afifah Septiana; Sanita Dhakirah; Lina Budiarti (Teewan Journal Solutions, 2026)
The growth of the outdoor equipment industry in Indonesia encourages companies to strengthen brand loyalty in order to retain consumers amid increasingly intense competition. Brand trust and brand experience are important factors influencing the formation of brand loyalty. This study aims to analyze the effect of brand trust and brand experience on brand loyalty toward Eiger products in Malang. The novelty of this study lies in examining the relationship between brand trust, brand experience, and brand loyalty among Eiger consumers in Malang City, which has received limited attention in previous studies. This research employed a quantitative method with questionnaires as the data collection technique. The sample consisted of 100 respondents selected using purposive sampling, with criteria aged 18–35 years, having purchased Eiger products at least twice, and made purchases within the last six months. Data analysis techniques included validity test, reliability test, multiple linear regression analysis, t-test, F-test, and coefficient of determination using IBM SPSS Statistics 27. The results showed that brand trust had a positive and significant effect on brand loyalty, brand experience had a positive and significant effect on brand loyalty, and both variables simultaneously had a positive and significant effect on brand loyalty with a contribution value of 64.6%. Based on the research findings, improving brand trust and brand experience contributes to increasing consumer brand loyalty toward Eiger products.